Gross Morphological Studies on the Liver and Gall Bladder of Sheep During Prenatal and Postnatal Development - Choudhury, A.R. (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on liver and gall bladder of prenatal and post-natal sheep below 1 year of age, to elucidate the gross changes during development. The liver appeared as a dark solid small mass like structure at 21.0 days old embryo just behind the developing heart under stereomicroscope. At 29.50 days of gestation, the liver was comprised of two similar lobes which were marked by cranial and caudal notches. At 42 days of gestation, it occupied almost whole of the abdominal space. At 140 days of gestation, the liver waspresent on the floor of the abdominal cavity and the right lobe of the liver was larger than that of the left one. Postnatal liver was firm and somewhat elastic to touch and quite friable and placed in the intrathoracic portion and entirely to the right of the abdominal cavity. The gallbladder of sheep was pear shaped hollowmusculomembranous sac localized in cystic impression. Colour of the gall bladder was transparent white at early gestational stages followed by light yellowish from mid stage onwards and finally it became greenish-black in color in post-natal stages.